Nanotechnology in Modern Animal Biotechnology 2019
DOI: 10.1007/978-981-13-6004-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials-Based siRNA Delivery: Routes of Administration, Hurdles and Role of Nanocarriers

Abstract: Ribonucleic acid interference (RNAi) is a potential alternative therapeutic approach to knock down the overexpression of genes in several disorders especially cancers with underlying genetic dysfunctions. For silencing of specific genes involved in cell cycle, small/short interfering ribonucleic acids (siRNAs) are being used clinically. The siRNA-based RNAi is more efficient, specific and safe antisense technology than other RNAi approaches. The route of siRNA administration for siRNA therapy depends on the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 176 publications
0
31
0
Order By: Relevance
“…Delivery of siRNAs into cells is very difficult since these are highly hydrophilic and polyvalent anionic midsized molecules. The major rate-limiting factor of siRNA's therapeutic activity is poor accumulation in the target tissue due to its easy degradation in blood by nucleases [ 25 ]. It is essential to find an efficient drug delivery system for siRNA-based drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of siRNAs into cells is very difficult since these are highly hydrophilic and polyvalent anionic midsized molecules. The major rate-limiting factor of siRNA's therapeutic activity is poor accumulation in the target tissue due to its easy degradation in blood by nucleases [ 25 ]. It is essential to find an efficient drug delivery system for siRNA-based drug development.…”
Section: Discussionmentioning
confidence: 99%
“…These bioengineered nanocarriers can act as effective therapeutic agents due to less toxicity, size, charge, and chemical modification capacities that protect the siRNA loaded nanocarriers from acid/enzymatic degradation and rapid elimination from local and systemic circulation. Studies have revealed the inefficiency of RNAi therapies is primarily due to inadequate delivery of siRNA, resulting in unfavorable immune response ( Sajid et al., 2020 ), ( Gupta, Rai, Jangid, Pooja, Kulhari ). So, extensive research is being conducted to obtain suitable siRNA conjugated nanocarriers having ideal characteristics like stability, biodegradability, biocompatibility that can o deliver siRNA at the target site without any immune responses (phagocytosis).…”
Section: Current Drawbacks and Challenges Of Chemotherapeutic Drugs A...mentioning
confidence: 99%
“…Thus, the ideal diameter of the RNAi molecules should range from 20 to 100 nm. 38 When the RNAi molecules reach the target tissue, they will be hindered by the endothelial lining of tissues that have pores with sizes from 4.5 to 25 nm. 20,38 Even if the RNAi molecules bypass the nuclease activity in different body systems (e.g., digestive and respiratory), serum, and extracellular matrix, the negative charge and relatively large size could constrain its cellular uptake.…”
Section: ■ Defensive Barriers Affect the Delivery And Uptake Of Rnai ...mentioning
confidence: 99%
“…38 When the RNAi molecules reach the target tissue, they will be hindered by the endothelial lining of tissues that have pores with sizes from 4.5 to 25 nm. 20,38 Even if the RNAi molecules bypass the nuclease activity in different body systems (e.g., digestive and respiratory), serum, and extracellular matrix, the negative charge and relatively large size could constrain its cellular uptake. 38,39 In addition, endolysosomal compartments are another barrier that could degrade RNAi molecules by endosomal engulfing.…”
Section: ■ Defensive Barriers Affect the Delivery And Uptake Of Rnai ...mentioning
confidence: 99%